Human blood-based electronic transistor. (1st January 2012) - Kosta, Shiv Prasad; Bhatele, Mukta; Chuadhari, Jitendra Prasad; Upadhyay, Trushit; Soni, Dilip; Nema, S. Purnima; Kosta, Y.P.; Patel, Kalpesh N.; Vaghela, Piyush R.; Patel, Jaimin R.; Patel, Bhavin S.; Thakre, Lunika; et al.
For the first time, study on the 'human blood-based electronic transistor' (HBBET) is presented. Effects of variables like blood temperature, blood flow rate, and distance between the forming probes on the input/output characteristics as well as current gain factor β of the transistor are studied. Emerging applications of bio-material human tissue blood electronic circuits towards cyborg implants, human-machine interface, human disease detection/healing, human health sensors and digital signal processing is visualised.